The Prevent Ovarian Cancer Program (POCP): Identification of Women at Risk for Ovarian Cancer Using Complementary Recruitment Approaches. Issue 8 (August 2021) - Tone, Alicia A.; McCuaig, Jeanna M.; Ricker, Nicole; Boghosian, Talin; Romagnuolo, Tina; Stickle, Natalie; Virtanen, Carl; Zhang, Tong; Kim, Raymond H.; Ferguson, Sarah E.; May, Taymaa; Laframboise, Stephane; et al.
Abstract : (Abstracted from Gynecol Oncol 2021;162:97–106) High-grade serous ovarian cancer (HGSOC) accounts for 70% of ovarian cancer cases and is the deadliest subtype of ovarian cancer. Approximately 20% of ovarian cancers are hereditary, and the greatest single risk factor for ovarian cancer is the inheritance of a pathogenic variant (PV) such as BRCA1 or BRCA2 .